FENOMENA TRIAL BY SOCIAL MEDIA TERHADAP ASAS PRADUGA TAK BERSALAH DIKAITKAN PADA PRINSIP DUE PROCESS OF LAW DALAM SISTEM PERADILAN PIDANA INDONESIA - Willson Chandra Happier willson; M. Ekaputra; Sutiarnoto (Universitas Islam Negeri Mataram, 2026)
The rapid development of social media in the digital era has given rise to the phenomenon of trial by social media, which refers to public judgment of an individual before a final and legally binding court decision is rendered. This phenomenon has the potential to undermine the principle of the presumption of innocence and the concept of due process of law, as public opinion is often formed more quickly than the legal process itself. Consequently, the reputation of individuals involved in legal proceedings may be adversely affected, while the objectivity and independence of law enforcement institutions may be compromised by public pressure. This study aims to analyze the impact of trial by social media on law enforcement in Indonesia, examine its implications for the protection of the presumption of innocence from the perspective of due process of law, and formulate an ideal legal framework to mitigate its negative effects on the criminal justice process. This research employs a normative legal research method supported by empirical data obtained through interviews. The study is descriptive-analytical in nature and utilizes primary, secondary, and tertiary legal materials collected through library research and document analysis. The data were analyzed qualitatively using a statutory approach. The findings indicate that trial by social media significantly affects law enforcement in Indonesia by shaping public opinion prior to judicial decisions, thereby potentially violating the presumption of innocence and disrupting the implementation of due process of law. Furthermore, public judgment on social media may influence the objectivity of judicial proceedings and create social stigma against suspects or defendants. Therefore, a more comprehensive legal framework is required, including the establishment of specific regulations governing the publication of criminal cases, stronger personal data protection mechanisms, reforms of the Criminal Procedure Code that accommodate digital rights, and the enhancement of public digital literacy as well as the professionalism of law enforcement officials. These measures are essential to ensure a fair, objective, and just judicial process in the digital age.